Der Dritte Teil der Clavierübung von Johann Sebastian Bach: Musik - Text - Theologie - Clement, Albert 1962- (Bonn Butz, 2017)
The fundamental work on Johann Sebastian Bach's most extensive and important organ cycle with analyses and interpretations that are as captivating as they are surprising, written by Prof. Albert Clement, one of the leading international experts on questions of interdisciplinary connections between musicology, organ and theology.The first edition of this standard work, published in the Netherlands, is now available in a slightly revised and expanded form in the Butz book programme.
Keywords: Bach, Johann Sebastian -- 1685-1750; Organ; Musical analysis; Music philosophy and esthetics